Tindak Tutur Ilokusi Pada Film Sujud Terakhir Bapak Karya Reka Wijaya - Setyawati, Andien; Kasnadi, Kasnadi; Ismail, Ahmad Nur; Ristiana, Rita (Jurnal Bahasa dan Sastra, 2026)
This study analyzes illocutionary speech acts in the film Sujud Terakhir Bapak by Reka Wijaya, which are utterances with specific purposes and meanings. This study aims to describe the forms and impacts of these illocutionary speech acts. Using a qualitative descriptive method and a pragmatic approach, primary data were taken directly from the film, while secondary data came from relevant books and journals. The data collection techniques used were free listening and note-taking techniques, then analyzed through data reduction, data presentation, and drawing conclusions. John Searle’s speech act theory was used as a basis. Of the total 95 speech data, 92 data were found to be forms of illocutionary speech acts, consisting of 30 assertive data, 28 directive data, 18 expressive data, 5 commissive data, and 7 declarative data. Meanwhile, 3 speech data showed illocutionary impacts in the form of conflict, emotional shock, and spontaneous and surprised reactions. This study concluded that the film is rich in all five forms of illocutionary speech acts that cause various impacts. It is hoped that future researchers will be more careful in understanding the theory when analyzing illocutionary speech acts.